Brand Strategy in the Era of Electric Vehicles : Researching the brand strategies of some of the largest vehicle manufacturers in the shift towards EVs - Gustafsson, Lisa; Holster Krantz, Lukas (My University, 2022)
A paradigm shift is underway in the automotive industry. Most of the largest vehicle original equipment manufacturers are transitioning their internal combustion engine passenger vehicle production to electric. This transition is a challenge not only from an engineering or production point of view but from a brand perspective as well. The brand strategy for new technology is hard to navigate. What constitutes a brand is in and of itself a complex matter, as multiple definitions exist (Kapferer 2004). The difficulty in determining which strategy is used subsequently makes it difficult to determine what advantages and disadvantages come with which strategy. When there is a disruptive change in technology, incumbent companies that are ” too big to fail”, can fail. New actors can use this disruption to enter the market and position themself to quickly gain market share. This thesis maps out what brand strategies are deployed by some automotive companies in Europe and the USA, and how these might impact the company's abilities to survive the transition. The study gathers and analyses marketing material, press releases, and annual reports to determine the vehicle manufacturers’ brand strategies, goals for electrification, and past electric vehicle sales. Two semi-structured interviews are performed alongside the data gathering. One interview with an incumbent, Volkswagen, and one interview with a new entrant, Polestar. These add depth from two different points of view to the reasoning behind chosen brand strategies. The research revealed that product-line extension, sub-branding, and rebranding of the main brand (or new main brand creation) are the brand strategies deployed by the manufacturers included in the research. Sub-branding is the most common and product-line extension is the least common strategy among the investigated manufacturers. Most manufacturers seem to be headed towards a complete rebranding strategy, however. Product-line extension is revealed through the interviews to come with the most disadvantages of the brand strategies deployed by the researched manufacturers. This is even though Volkswagen themselves has deployed such a strategy. The disadvantages include not being flexible, being overly expensive, time-consuming, and confusing for the customer. It is also more difficult to convert existing models to electric and use their existing brands, as compared to creating completely new models and brands, from a manufacturing perspective. Sub- branding is revealed as a good middle ground for now. New electric vehicle models come with higher trust in their capabilities as compared to converted models. This strategy is more flexible than product-line extension as the positive aspects of the corporate brand can be handpicked and inserted in the sub-brand alongside new brand attributes preferable for electric vehicles. The only major disadvantage discovered through the interviews is the expense of garnering enough attention for a new sub-brand, where existing sub-brands already have awareness. The research concludes that the manufacturers with a complete rebranding of the main brand (or new main brand) enjoy the most success in ramping up their electric vehicle sales. However, the research also reveals that such action can not be taken by most manufacturers due to their high economic reliance on continuing to manufacture and sell internal combustion engines. Some psychological factors are also discussed as possible underlying reasons for the reluctance to deploy this strategy. Positive heritage attributes are revealed as a useful and important tool to use in transitioning the brand and when creating new sub-brands. Finally, the research concludes that a successful brand strategy for surviving the transition includes creating new sub-brands and moving towards a complete rebranding of the main brand at a pace that is compatible with the manufacturing capabilities. Spending resources on product-line extensions are wasteful and either moving too quickly or too slowly in the rebranding effort of the main brand risks hurting the credibility of the manufacturer.
Keywords: technology shift; electric vehicles; brand strategy; automotive industry; heritage